A Study on Bluetooth Security Connection and Attacks - Dukitha, M; Harikrishnan, D (International Journal of Computer Sciences and Engineering, 2025)
Increasing popularity of wireless communication systems, Bluetooth has become one of the most widely used short range wireless protocols. Unfortunately, due to the nature of wireless communication networks, Bluetooth has security vulnerabilities particularly through eavesdropping. Despite newer and more secure versions of Bluetooth being released, older versions such as Bluetooth four.0 and 4.1 are still widespread all over the world. After thoroughly exploring the current Bluetooth security model and reasons for potential vulnerability, this report performs a comparative analysis of different Bluetooth security attacks, extending them and applying them to readily accessible devices, and offering countermeasures. Based on our results and discussion, it's clear that Bluetooth is a widespread technology with significant security vulnerabilities in the real world today.